Efficacy of Social Accounting Practices on the Financial Performance: Evidence from Ethiopia - S M, Uvaneswaran; Zemen, Tsega; Muhammed, Seid (Journal of Innovation in Business and Economics, 2019)
This aims of this paper is to examine the effects of social accounting practices on the financial performance of business organizations in the city of  Dessie, South Wollo, Ethiopia. To fulfill this objective, a stratified-random sampling design was used, followed by proportional sampling techniques. The research data were obtained from primary and secondary sources and analyzed using multiple linear regression to understand the effect of corporate social responsibility accounting practices on financial performance. The results of the study indicated that report on social accounting was indeed necessary, however, there was no standard guideline followed when reporting except the Ethiopian commercial code and statement of socio-economic operations. Likewise, the observation during this research showed that an increase in corporate social responsibility scores would lead to an increase in the company's financial performance.